Excess mortality during COVID-19 in 5 european countries and a critique of mortality data analysis - Jorge Manuel Félix Cardoso (2020)
Intro The COVID-19 pandemic is an ongoing event disrupting lives, health systems, and economies worldwide. Clear data about the pandemic's impact is lacking, namely regarding mortality. Its impact on all-cause mortality can be direct, due to deaths by COVID-19, but also indirect, through pandemic-oriented changes in healthcare organizations and peoples' behaviours. Aim This work aims to study the impact of COVID-19 through the analysis of all-cause mortality data made available by different european countries, and to critique their mortality surveillance systems. Methods European countries that had publicly available data about the number of deaths per day/week were selected (England and Wales, France, Italy, Netherlands and Portugal). Two different methods were selected to estimate the excess mortality due to COVID19: deviation from the expected value from homologue periods, and remainder after seasonal time series decomposition. We estimate total and age-specific all-cause excess mortality. Furthermore, we compare different policy responses to COVID-19 regarding health care and social distancing. Results Excess mortality is found in all 5 countries, ranging from 6.3% in Portugal to 81.5% in Italy. Furthermore, excess mortality is likely higher than COVID-attributed deaths in 4 of the 5 countries. Discussion The impact of COVID-19 on mortality appears to go far beyond the officially attributed deaths, but with varying degrees in different countries. Different policies may explain part of this difference. Comparisons between countries would be useful, but are difficult due to large disparities in mortality surveillance systems. A generalized lack of cause-specific mortality data and unreliable data for all-cause mortality undermines the understanding of the impact of policy choices on both direct and indirect deaths during COVID-19. Nonetheless, from the studied countries, the Portuguese mortality surveillance system appears to be the most accurate and reliable.